2023
DOI: 10.3389/fpls.2023.1119041
|View full text |Cite
|
Sign up to set email alerts
|

Insights into taxonomy and phylogenetic relationships of eleven Aristolochia species based on chloroplast genome

Abstract: IntroductionThe Aristolochia, as an important genus comprised of over 400 species, has attracted much interest because of its unique chemical and pharmacological properties. However, the intrageneric taxonomy and species identification within Aristolochia have long been difficult because of the complexity of their morphological variations and lack of high-resolution molecular markers.MethodsIn this study, we sampled 11 species of Aristolochia collected from distinct habitats in China, and sequenced their compl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 54 publications
5
5
0
Order By: Relevance
“…Overall, the 31 plastid genomes of Linderniaceae showed size differences mainly in the LSC region ( Table 2 ). Consistent with previous studies ( Yang et al., 2022 ; Bai et al., 2023 ; Peng et al., 2023 ), the non-coding and single copy (SC) regions were more divergent than the coding and IR regions ( Supplementary Figure 3 ). We, therefore, speculated that the size variation of Linderniaceae plastomes was mainly attributed to the LSC region, especially in the non-coding regions, similar to the results of studies of Gao et al.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Overall, the 31 plastid genomes of Linderniaceae showed size differences mainly in the LSC region ( Table 2 ). Consistent with previous studies ( Yang et al., 2022 ; Bai et al., 2023 ; Peng et al., 2023 ), the non-coding and single copy (SC) regions were more divergent than the coding and IR regions ( Supplementary Figure 3 ). We, therefore, speculated that the size variation of Linderniaceae plastomes was mainly attributed to the LSC region, especially in the non-coding regions, similar to the results of studies of Gao et al.…”
Section: Discussionsupporting
confidence: 90%
“…Consistent with previous studies (Azarin et al, 2021;Zhao et al, 2022;Li et al, 2023), Leucine (Leu) was the most frequent amino acid, and cysteine (Cys) was the least common. In Linderniaceae, codons mainly ended with A and U when the RSCU value was greater than 1, and codons primarily ended with G and C when the RSCU value was below 1, which appears to be a common phenomenon in gene expression of land plants (Cui et al, 2019;Chakraborty et al, 2020;Gao et al, 2022;Bai et al, 2023;Zhou et al, 2023). Moreover, the GC content of synonymous third codons positions (GC3s) showed that AT content was more abundant in the protein-coding genes (Supplementary Table 5), which may be correlated with the abundant AT content of plastid genomes.…”
Section: Evolution Of Protein-coding Genes In Linderniaceaementioning
confidence: 99%
“…To determine the degree of variation in these highly variable regions in C. nannophylla, the nucleotide variability in DNASP v6 was used to identify differences among the cp genomes of Clematis and mutation hotspots. Nucleotide diversity (Pi) indicates the degree of variation in the nucleic acid sequences in each species, and sites with high variability can be selected as molecular markers for population genetics [49,54]. In the present study, the results of the nucleotide diversity analysis showed that the gene sequences in the LSC and SSC regions were more variable than those in the IR regions, which is consistent with the results found in Asteraceae and Fagaceae plants [49,59].…”
Section: Codon Usage Bias In the Cp Genome Of C Nannophyllasupporting
confidence: 91%
“…Simultaneously, the same highly variable regions, ccsA and rpl32, were also found in Fagus longipetiolata of Fagaceae. The ccsA gene is also considered to be the locus for understanding cp genome evolution in Fagus longipetiolata of Fagaceae [49], Litsea [54], Pterocarpus [51], and Prosopis genera [55]. Furthermore, the Pi values of 13 height-variable regions in this study were all higher than 0.006, corresponding to the height-variable region.…”
Section: Codon Usage Bias In the Cp Genome Of C Nannophyllamentioning
confidence: 58%
“…The IR junctions in Thottea are identical to certain species of Aristolochia subgenus Siphisia (Figure 3). Bai et al (2023) identified similar IR boundary variations among the Aristolochia subgenera, albeit not considering all available data, therefore lacking resolution. The new sequence data created in their study was not publicly available in time for inclusion here.…”
Section: Discussionmentioning
confidence: 99%